2017
DOI: 10.1080/2162402x.2016.1278100
|View full text |Cite
|
Sign up to set email alerts
|

PDL1 expression is a poor-prognosis factor in soft-tissue sarcomas

Abstract: Soft-tissue sarcomas (STS) are a group of rare, heterogeneous, and aggressive tumors, with high metastatic risk and relatively few efficient systemic therapies. In the quest for new treatments, the immune system represents an attractive therapeutic target. Recently, PD1/PDL1 inhibitors showed very promising results in patients with solid tumors. PDL1 expression has been rarely studied in STS, in small series only, by using immunohistochemistry (IHC), and with non-concordant prognostic implications. Here, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 83 publications
4
69
0
Order By: Relevance
“…Recently, using IHC, numerous studies have reported PD‐L1 protein expression in different types of cancer . Given that PD‐L1 DNA amplification was rare in our study, the expression of PD‐L1 was mainly regulated by many kinds of signalling pathway as a downstream effector instead of an upstream initiator.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Recently, using IHC, numerous studies have reported PD‐L1 protein expression in different types of cancer . Given that PD‐L1 DNA amplification was rare in our study, the expression of PD‐L1 was mainly regulated by many kinds of signalling pathway as a downstream effector instead of an upstream initiator.…”
Section: Discussionmentioning
confidence: 67%
“…Recently, using IHC, numerous studies have reported PD-L1 protein expression in different types of cancer. [19][20][21] Given that PD-L1 DNA amplification was rare in our study, the expression of PD-L1 was mainly regulated by many kinds of signalling pathway as a downstream effector instead of an upstream initiator. Lu et al found that MLL1 could inhibit PD-L1 mRNA expression by decreasing the level of trimethylation of histone 3 lysine 4 in the PD-L1 promoter.…”
Section: Discussionmentioning
confidence: 83%
“…T-cell infiltration and PD-L1 expression were found to be higher in sarcomas with complex genomics and particularly in UPS than in other STS [87, 88]. Among STS subtypes, UPS/MFS has the highest median macrophage infiltration and the infiltration of immature dendritic cells was positively correlated with survival.…”
Section: Immunotherapymentioning
confidence: 99%
“…On the other hand, the assessment of the action of PD-1/ PD-L1 blockers as well as the prognostic value of PD-1/PD-L1 expression in soft-tissue sarcomas have been studied only in the last years 5 and there is a shortage of studies on PD-1/PD-L1 expression in KS. Furthermore, the results of these studies appear controversial, since Chen et al 6 failed to find cases that expressed detectable PD-L1 among 9 KS patients, while Paydas et al 7 found PD-1 and/or PD-L1 expressed in 80% of KS patients belonging to their case series.…”
Section: Pd-l1 Expression In Tumour Microenvironment Supports the Ratmentioning
confidence: 99%